Analysis of cost and factors related to the return of medication to the hospital pharmacy of a private hospital in the City of Belem (Research, Society and Development, 2021)
Objective: analysis of reasons and costs related to the return of medication, after distribution, to the hospital pharmacy. Methods: This is a quantitative retrospective study in which the costs of returns from patients admitted to clinical and surgical units were evaluated, using the computerized hospital management system SOUL MV®. Results: the reasons and costs involved in the return of these products in the years 2018, 2019 and 2020, respectively, are expressed. A total of R$2,870,733.19 was declared. It is observed that in 2018 when the collective SDM was used, the return cost was BRL 1,161,956.41, equivalent to 40.4% of the total cost. In 2019 and 2020, with the single dose individualized system, expenses were reduced to 31.9% and 27.6%, respectively. The drug deadline was the most predominant (57.1%), followed by material in disagreement (9.2%), prescription suspension (8.2%), unused material (7.2%), duplicity (6 .1%), patient and/or procedure refusal (2.4%), incorrect request (2.1%), death (1.2%), patient transfer (0.5%) and procedure suspended (0.2%). Conclusion: The results of the study demonstrate that the use of individualized unit dose SDM significantly reduced return costs and drug-related errors. This practice can bring savings to health services when the returned medications are in a condition suitable for reuse by another patient. However, reuse requires discussion and planning, as the safety and success of treatments depend on care during storage.